If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -3y = 9 + -4y Solving 3 + -3y = 9 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 3 + -3y + 4y = 9 + -4y + 4y Combine like terms: -3y + 4y = 1y 3 + 1y = 9 + -4y + 4y Combine like terms: -4y + 4y = 0 3 + 1y = 9 + 0 3 + 1y = 9 Add '-3' to each side of the equation. 3 + -3 + 1y = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 9 + -3 1y = 9 + -3 Combine like terms: 9 + -3 = 6 1y = 6 Divide each side by '1'. y = 6 Simplifying y = 6
| (x+7)=(24+26) | | y-1=3(x+6) | | y-5=3(x-1) | | 67-4x=5x+18 | | 8x+v=3x+w | | 8-9x=89-30x | | Y=mx+bx | | y+2=-6(x+6) | | T=3+1.25(13) | | 6x+36=15x-54 | | 6x-5=-3 | | 8y-2=13y+33 | | 5(5x-4)-4(3x-6)= | | -46-2x=8-8x | | -4-6n=7n+3 | | 2x-6x=4x+3 | | T=3+1.25c | | -4n-6=7n+3 | | 3(4x+1)+2(6x-9)= | | 5h-3h+9h=176 | | 12500=.5x^2+11x+4000 | | -4m=28 | | 48=7t-3t | | 7(x+7)+5(2x-8)= | | 2y+5+4y=6y+3 | | -3+7=-10 | | 2x^2=450 | | y+4y=95 | | (2x-1)(3x+5)=0 | | -36=j+13 | | 8f+4e=16 | | 3(x+4)+4(x-6)= |